(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2025)
The purpose of this research was to apply modern technologies, especially "additive manufacturing technology", in order to improve the competitive economic performance of the unit under study. The Dental Manufacturing and Orthodontics CenterAl-Moatham was chosen as the field of application and generalization of the results reached by the research to all units within the work environment. To achieve the research goal, work will be done to study and analyze the costs adopted in the center, analyze them and then improve competitive performance using advanced technology. The research reached many conclusions, the most important of which is that additive manufacturing technology (3D printer) leads to reducing waste, reducing production time, reducing waste and use of materials, and dispensing with a large number of workers, and then reducing costs and thus improving competitive performance.